Krležin Aretej, ili legenda o svetoj Ancili, rajskoj ptici u prijevodu Zoltána Csuke - Bockovac, Timea (SlavVaria, 2023)
Krleža’s Aretej, or the Legend of Saint Ancilla, the Bird of Paradise, translated by Zoltán Csuka. The present paper discusses the description and analysis of Zoltán Csuka’s translation procedures in Krleža’s play Aretej, or the Legend of Saint Ancilla, the Bird of paradise. In the introductory part, there is an insight into the theoretical framework of translation given, with special reference to the challenges of artistic translation, which, in addition to the linguistic ones, also require intercultural competence. The paper also discusses Csuka’s promotional and Krleža’s literary activities. In the central part of the text, there is an example analyzed at the semantic level with the aim of determining the quality of the resulting translation, the literary text entitled Aretaeus, avagy legenda Szent Ancilláról, a mennyei madárról.